ANALISIS PENERAPAN INFRASTRUKTUR TEKNOLOGI INFORMASI PADA PT TVMI UNTUK MENINGKATKAN EFISIENSI OPERASIONAL DISTRIBUSI - Adelitan Salsabilah Amir; Charles Yandhika; Kennan Hamilton; Darriel Dapples; Dicky Pratama (CV. Denasya Smart Publisher, 2026)
Advances in information technology have encouraged distribution companies to enhance service quality and operational effectiveness through the use of adequate IT infrastructure. PT TVMI is a company engaged in the sales and distribution of Toshiba televisions in Indonesia. Its operational activities—such as inventory management, transaction recording, goods distribution, and after-sales services—require the support of an integrated IT infrastructure. This study aims to analyze the IT infrastructure requirements at PT TVMI and to design recommendations for their implementation with reference to the Information Technology Infrastructure Library (ITIL) framework. The research methods used include needs analysis, gap analysis, and IT service process mapping based on ITIL domains. The results indicate that PT TVMI must modernize its IT infrastructure through the development of an integrated information system, the improvement of IT service procedures, the strengthening of information security, and the enhancement of IT human resource capabilities. The application of the ITIL framework is expected to improve the effectiveness of distribution operations, minimize system downtime, increase the accuracy of inventory data, and enhance coordination between work units.